2015
DOI: 10.1021/es506118e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Monochloramine Treatment on Colonization of a Hospital Water Distribution System by Legionella spp.: A 1 Year Experience Study

Abstract: Contamination of hot water distribution systems by Legionella represents a great challenge due to difficulties associated with inactivating microorganisms, preserving the water characteristics. The aim of this study was to examine over the course of 1 year in 11 fixed sites, the impact of monochloramine disinfection on Legionella, heterotrophic bacteria (36 °C), Pseudomonas aeruginosa contamination, and chemical parameters of a plumbing system in an Italian hospital. Three days after installation (T0), in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…After conversion to monochloramine disinfection within BWSs, there were reductions in the number of distal sites testing positive for Legionella (39–100% to 0–18% positivity); however, there was a large range in the log reduction of Legionella levels (0.2 to 3 log 10 CFU L −1 ) with one study reporting no changes in levels post-conversion during the one- to three-year monitoring period [ 58 , 59 , 60 ]. Control of biofilm-associated Legionella was also observed [ 58 , 61 ], most likely due to the better penetration of monochloramine into biofilms compared to chlorine [ 62 ]; however, control of biofilm-associated L. pneumophila (Lp) was previously reported to be pipe material specific during chlorine and monochloramine treatment [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…After conversion to monochloramine disinfection within BWSs, there were reductions in the number of distal sites testing positive for Legionella (39–100% to 0–18% positivity); however, there was a large range in the log reduction of Legionella levels (0.2 to 3 log 10 CFU L −1 ) with one study reporting no changes in levels post-conversion during the one- to three-year monitoring period [ 58 , 59 , 60 ]. Control of biofilm-associated Legionella was also observed [ 58 , 61 ], most likely due to the better penetration of monochloramine into biofilms compared to chlorine [ 62 ]; however, control of biofilm-associated L. pneumophila (Lp) was previously reported to be pipe material specific during chlorine and monochloramine treatment [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to achieve control of Legionella proliferation, the national and international directives point out several disinfection strategies, based on chemical disinfectants (i.e., chlorine dioxide, monochloramines, and hydrogen peroxide) and physical treatments [i.e., ultraviolet (UV) light and hot temperature treatments]. All of them have shown some advantages and disadvantages (Mcdonnell and Russell, 1999 ; Richardson et al, 2007 ; Lin et al, 2011 ; Mancini et al, 2015 ; Girolamini et al, 2019 ). However, some authors have shown how these treatments, especially the use of chemical disinfectants, could select resistant strains and introduce some changes in the bacterial genome.…”
Section: Introductionmentioning
confidence: 99%